Does Modern Technology Increase Agricultural Productivity? Revisiting the Evidence from Loevinsohn et al. - Herdt, Robert W.; Mine, S. (CGIAR Independent Science and Partnership Council, 2017)
This technical note re-examines the 214 papers identified by Loevinsohn and colleagues in their 2013 report to the UK Department for International Development (DFID) on the circumstances and conditions under which technology adoption results in increased agricultural productivity. That report produced no clear evidence-based guidance on such circumstances and conditions. Using criteria slightly less restrictive than theirs, the authors of this paper identified 30 of the 214 studies that reported a relationship between technology and agricultural productivity: 21 of the 23 with yield data showed a positive relationship between use of technology and yield, and 2 showed no increase; 24 of 26 examining income showed a positive relationship between technology use and income, and the other 2 showed no increase.